Investigating the Role of Development Banks, Their Services, and Ranking them in their home Countries (International Journal of Applied Research in Management and Economics, 2018)
The basis for progress in any country is possible with the comprehensive support of important and infrastructural projects in various economic, cultural, and developmental fields. One of the most important supporting structures for these projects is development banks. However, the important point in this banking structure is to review and continuously update the current processes in order to maximize their efficiency. By studying and comparing the status and services of development banks in Iran with other development banks of countries with a favorable economic status, this study aims to investigate and improve the processes in the development banks of Iran. For this purpose, firstly, the selected countries of each continent were identified from the perspective of three economic indicators of gross national income (GNI), gross domestic product(GDP), and gross domestic product-purchasing power parity(GDP-PPP). Then, by examining databases such as Swift, the development banks of each of these countries were extracted, and their services and processes were identified and reviewed. By examining the results of this research, it becomes clear what the main and support activities of development banks are, which of the selected countries in each continent are the most successful in terms of the aforementioned economic indicators, and which development banks in the selected countries are the best.